CRIMINAL LAW PERSPECTIVE ON CYBERBULLYING PHENOMENON ON SOCIAL MEDIA - Silalahi, Keisha Anakku Putri; Sidauruk, Jinner; Gultom, Meli Hertati (DE'RECHTSSTAAT, 2024)
Cyberbullying in Indonesia has become a serious concern in recent years, with the increased use of digital technologies such as social media and instant messaging applications as the main platforms. This phenomenon not only includes various forms such as insults and threats, but also seriously impacts the mental health of victims, including high levels of stress, anxiety, and depression. The ITE Law and the Criminal Code provide the legal foundation to address cyberbullying, although implementation still faces challenges in consistency and effectiveness of law enforcement. Effective prevention strategies, such as education on digital etiquette and public awareness raising, are needed to reduce the incidence of cyberbullying in Indonesia. Active cooperation between the government, educators, technology platforms, and communities is key to creating a safe and supportive online environment for all technology users, particularly the younger generation who are most vulnerable to the negative impacts of cyberbullying.